Proceedings of the 4th International Conference on Electrical and Information Technologies for Rail Transportation (EITRT) 2019 : Novel Traction Drive Technologies of Rail Transportation /: Novel Traction Drive Technologies of Rail Transportation. (2020) - Unknown
No abstract available